2003
DOI: 10.1002/mc.10144
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic expression of the H19 gene during spontaneous hepatocarcinogenesis in the albumin SV40 T antigen transgenic rat

Abstract: Previous studies in this laboratory have demonstrated that the earliest cytogenetic alteration in the development of hepatic neoplasms in a transgenic strain of rats bearing the albumin Simian virus 40 T antigen (Alb SV40 T Ag) construct was a duplication of the chromosome 1q4.1-1q4.2 band. In this region, in the rat genome a cluster of linked imprinted genes occurs. One of these imprinted genes, H19, which is expressed in fetal liver but not in adult liver, was found to be expressed in virtually all neoplasms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…Interestingly, H19 RNA is upregulated in HBV-associated HCC [30]. Furthermore, a biallelic expression of H19 gene was found in human HCC patients [31] and in liver neoplasms of albumin SV40 T-antigen-transgenic rats [32].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, H19 RNA is upregulated in HBV-associated HCC [30]. Furthermore, a biallelic expression of H19 gene was found in human HCC patients [31] and in liver neoplasms of albumin SV40 T-antigen-transgenic rats [32].…”
Section: Introductionmentioning
confidence: 99%
“…One of the better elucidated large ncRNAs is Xist (X chromosome inactive specific transcript) that presents as a 17-kb (human) and a 15-kb (mouse) molecule responsible for somatic X-chromosome dosage compensation (Brockdorff et al, 1992;Brown et al, 1992;Plath et al, 2002). Another example is a paternally imprinted gene H19 (O'neill, 2005), with a conserved secondary structure but non-conserved ORFs, that functions as a tumor suppressor in some tumor types and may play a significant role in tumorigenesis in other types (Steenman et al, 1994;Lottin et al, 2002;Manoharan et al, 2003). Recently, Willingham et al (2005) identified an ncRNA designated NRON that is a repressor of nuclear factor of activated T cells.…”
Section: Introductionmentioning
confidence: 99%
“…H19 has been shown to follow the same expression patterns as Igf2 in both the mouse and rat, although it is expressed from the opposite allele 17. While Igf2 is expressed exclusively from the paternal allele, H19 is expressed solely from the maternal allele.…”
Section: Resultsmentioning
confidence: 99%
“…The cytogenetic changes during the development of hepatomas in the transgenic rat have been shown to be quite similar to those during virally‐ and chemically‐induced hepatoma development 16, and it is for that reason that our lab is attempting to further characterize the process of hepatocarcinogenesis in the SD Alb SV40 T Ag transgenic rat. Dragan et al 16 and Manoharan et al 17 have previously shown the duplication of 1q3.7‐4.3 correlates with re‐expression of Igf2 and H19 in most female hepatic neoplasms of the SD Alb SV40 T Ag transgenic rat. Additionally, Manoharan et al determined that expression of H19 in these hepatic neoplasms was biallelic, which implied a loss of regulation at the Igf2 / H19 locus 17.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation